The essence of the human: identity, memory, testimony and trauma in the work “Is this a man?” from Primo Lévi - Camargo, Cássio Michel dos Santos (2019)
This article aims at analyzing the work “Is This a man?” by Primo Levi, establish links between the concepts of memory and identity, highlighting how the internal logic of Auschwitz the impossibility of maintaining individual identity. Tries to demonstrate how the “experience unreasonable” within the camps is a traumatic memory from the analysis of the testimony of Levi, the work of the authors references in thematic collective memory and individual identity and traumatic memory. Among those used Halbawachs Catroga and in the context of the constitution and uses of memory; M. Pollack to issues of identity; Paul Ricoeur regarding the work of mourning and forgiveness, Bauman Zygmunt aspects about the Holocaust, H. Arendt on Violence and coercive aspects and Eric Hobsbawm, in a historical context of World War II.